Role of Epithelial-Mesenchymal Transition in Pancreatic Ductal Adenocarcinoma: Is Tumor Budding the Missing Link? - Karamitopoulou, Eva (Frontiers in Oncology, 2013)
Pancreatic ductal adenocarcinoma (PDAC) ranks as the fourth commonest cause of cancer death while its incidence is increasing worldwide. For all stages, survival at 5 years is<5%. The lethal nature of pancreatic cancer is attributed to its high metastatic potential to the lymphatic system and distant organs. Lack of effective therapeutic options contributes to the high mortality rates of PDAC. Recent evidence suggests that epithelial-mesenchymal transition (EMT) plays an important role to the disease progression and development of drug resistance in PDAC. Tumor budding is thought to reflect the process of EMT which allows neoplastic epithelial cells to acquire a mesenchymal phenotype thus increasing their capacity for migration and invasion and help them become resistant to apoptotic signals. In a recent study by our own group the presence and prognostic significance of tumor budding in PDAC were investigated and an association between high-grade budding and aggressive clinicopathological features of the tumors as well as worse outcome of the patients was found. The identification of EMT phenotypic targets may help identifying new molecules so that future therapeutic strategies directed specifically against them could potentially have an impact on drug resistance and invasiveness and hence improve the prognosis of PDAC patients. The aim of this short review is to present an insight on the morphological and molecular aspects of EMT and on the factors that are involved in the induction of EMT in PDAC.